Influence of Socioeconomic, Demographics, and Prices Factors on Cooking Fuel Choice of Indonesian Households - Hadi Prasojo; Djoni Hartono (Jurnal Economia, 2023)
AbstractThere are differences in the choice of cooking fuel in Indonesian households. Some households still not yet used clean fuel for daily cooking, even though clean energy is crucial and included in the Sustainable Development Goals (SDGs). This study examines the influence of several factors on household's cooking fuel choice using SUSENAS data. This study is based on conceptual framework and theory on several determinant factors, including income, education level of the household head, and energy prices. The testing of the hypothesis used the probit methods. In the estimation results obtained, socioeconomic and demographic factors, namely income, education level of the household head, location of the household in urban areas, positively and significantly impacts the decision to choose clean fuel for cooking. Meanwhile, the price of clean fuel types such as LPG and city gas negatively and significantly impacts the decision to choose clean fuels for cooking in Indonesian households.Keywords: Demographic Factors; Socioeconomics Factors, Energy Prices; Cooking Fuel Choice, Probit